A Bluetooth intelligent e-healthcare system: analysis and design issues. (6th August 2008) - Tounsi, Mohamed; Qureshi, Basit
Many studies have shown that internet access in many countries had failed to penetrate the general public as expected. With less than 3% members of the public accessing the internet, it is evident that most of the useful applications offered by the internet are inaccessible. On the contrary, mobile phones are in great demand; smart phones in particular have an ever growing market. It is evident that with a greater number of mobile users, people can be facilitated with mobile accessible applications. Of many beneficial applications, one such application is providing remote healthcare on mobile devices. Much work has been done in this area of research; however, using Bluetooth, enabled smart phones with Wireless Application Protocol technology implementing an intelligent remote healthcare system has been proposed. A rule-based expert system can identify diagnosis for remotely located patients to offer location expert physicians and subsequent analysis can be delivered to the patient relieving him/her from frequent visits to a healthcare service provider thus reducing the load of patients on the existing infrastructure. This article presents design and implementation of one such system, Mobile Intelligent Remote Healthcare Monitoring System and discusses issues.